The aromatherapy use’s during labor: characterization of nurses' knowledge (Research, Society and Development, 2021)
Childbirth is a unique moment in the women pregnant life and the nursing, with its care and holistic model, manages to place the woman as the protagonist of the birth process, using tools such as aromatherapy. This study characterized the knowledge about aromatherapy and the use of essential oils (EOs) during labor (L) through a questionnaire applied to nurses at the Cândido Mariano Maternity and the Maria Aparecida Pedrossian University Hospital (MAPUH) maternity. From the results, it was possible to verify that 100% of professionals know aromatherapy. However, the percentage of 69.2% have technical training and the knowledge about the dilution way and application of EOs, the professionals do not prefer product brand, 100% use lavender essential oil (EO) and 61.5% use cinnamon EO in parturient. Thus, aromatherapy is already a regular practice among nurses in institutions, but adequate training is necessary, so that they can apply the practice safely and with scientific support.